Relationship of Intraocular Pressure with Central Aortic Systolic Pressure. (3rd March 2016) - Tsai, Andrew S. H.; Aung, Tin; Yip, Wanfen; Wong, Tien Yin; Cheung, Carol Yim-Lui
Abstract: Purpose : To examine the relationship between central aortic systolic pressure (CASP) and intraocular pressure (IOP), and to compare the strength of any association with that of peripheral blood pressure and IOP. Methods : Adults ranging in age from 40 to 80 years were consecutively recruited from the population-based Singapore Chinese Eye Study. We measured CASP using arterial tonometry (BPro) and IOP using Goldmann applanation tonometry. All participants had a standardized examination including a complete ophthalmic and systemic examination. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured using peripheral blood pressure cuff. Univariable and multiple linear regression analyses were performed to examine the relationship between CASP and IOP. Standardized regression coefficients (sβ) were calculated to compare the associations between CASP and SBP with IOP. Results : A total of 372 consecutive Chinese participants were analyzed. After adjusting for age, gender, body mass index, total cholesterol, use of antihypertensive medication and central corneal thickness, each 10 mmHg increase in CASP was associated with 0.32 mmHg of IOP elevation [95% confidence interval (CI): 0.10–0.53, sβ = 0.160, p value = 0.004]. SBP also had a positive relationship with IOP ( β = 0.279, 95% CI: 0.079–0.479, sβ = 0.152, p value = 0.006). Associations between IOP and CASP, SBP and DBP were similar in participants using antihypertensive medication to participant not using antihypertensives. Conclusions : Increased CASP, as measured by arterial tonometry, is associated with higher IOP. Our results strengthen the relationship between systemic blood pressure and IOP.